The Role of Reading by Analogy in First Grade Finnish Readers - Holopainen, Leena; Ahonen, Timo; Lyytinen, Heikki (Scandinavian journal of educational research, 2002)
Computer-based assessment of the use of beginning and end analogies based on clue syllables of five different syllable structures was developed to examine the role of analogy in beginning reading of a orthographically regular language, Finnish. Forty-seven Grade 1 children with a mean age of 7.5 years participated in the study. Unlike English, the most clear-cut result is that for all the syllable structures the use of clue syllables produced no significant differences in reading speed and accuracy of the following same beginning or same end syllables. The findings also show that the benefit to the readers varied according to the size of the syllables. No benefit was found in two letter syllables but some benefit was observed in three and four letter syllables for reading accuracy. Vowels and consonants have no clear effect on the use of analogy, probably in part because in Finnish all letters are sounded irrespective of their placement in a syllable. It is argued that the improvement from pre-test to test is due to phonological and orthographic similarities between the shared condition and clue syllables at the phoneme/letter level. Reading is based on single phoneme/letter analogies instead of the effect found in English where children benefit significantly from analogy based on larger units.